Colonialism is crime - Nielsen, Marianne O. (Critical issues in crime and society, 2019)
Introduction : crimes against indigenous peoples -- Breaking and bending the law historically -- Fraud, theft, and the trail of broken treaties -- Massacres to murder : violence against indigenous peoples -- Institutionalized torture and pedophilia : boarding schools for indigenous children -- Conquest by rape and violence : crimes against indigenous women -- The Conestoga indians, hate crimes, and domestic terrorism -- Stolen land to stolen oil : the theft of indigenous political economies -- Would you drink this water? : crimes of pollution and toxic dumping on indigenous lands -- Fighting back : colonial settler responsibilities and indigenous action.